The global foundations of public relations humanism, China and the West - Brown, Robert E. 1945-; St. John, Burton 1957-; Hou, Jenny Zhengye (Routledge, Taylor & Francis Group, 2022)
"The Global Foundations of Public Relations: Humanism, China and the West explores the growing humanistic turn in public relations processes and proposes that this has compelling parallels in the roots of Chinese philosophies. As the leader of growth and power across the Pacific Rim, public relations in China is not developing in isolation from the West, but via mutual accommodations and culturally complex interactions. By collecting cases and reflections on PR practices from both Chinese and Western scholars, the chapters propose that Chinese philosophies are playing a role in the development of modern Chinese PR practices, and - focusing less on the obvious differences and contracts - seek to highlight their spiritual, philosophical and political confluences. The conclusions drawn enhance and advance our understanding of public relations globally. This innovative work is of interest to educators and researchers in the fields of public relations, strategic communications, and public diplomacy. Robert E. Brown is Professor Emeritus at Salem State University, USA, and a member of the Affiliated Faculty of Emerson College. Burton St. John III is Professor of Public Relations at the University of Colorado-Boulder, USA. Jenny Zhengye Hou is Chief Investigator of Strategic Communication and Public Relations at Queensland University of Technology, Australia, and Senior Fellow of Higher Education Academy"--
Literaturangaben
Keywords: Geschichte; Öffentlichkeitsarbeit; Humanismus; Philosophie; China; Public relations / Cross-cultural studies; Humanism; Communication, International; Public relations; Cross-cultural studies; Aufsatzsammlung